PENGARUH PENERAPAN METODE EKSPOSITORI TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MURID KELAS V SD MUHAMMADIYAH PERUMNAS KOTA MAKASSAR - Wahyu Pratama; Suardi; Yumriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the expository method on students'learning outcomes in Social Studies (IPS) subjects for fifth-grade students at SDMuhammadiyah Perumnas, Makassar City. This research employed a quantitativeapproach using a pre-experimental design with a one-group pretest-posttestdesign. The study involved 17 students, consisting of 7 boys and 10 girls. Datawere collected through pretest and posttest assessments and analyzed usingdescriptive and inferential statistics through a paired sample t-test. The analysisresults showed an increase in the average student score from 66.47 (pretest) to82.65 (posttest), with a difference of 16.18 points. The normality test indicated thatthe data were normally distributed (significance = 0.200), and the t-test resultsshowed a significant difference between the pretest and posttest scores(significance = 0.000< 0.05). Therefore, it can be concluded that the expositorymethod has a significant effect on improving studentsSocial Studies learningoutcomes. This method is effective for classroom instruction because it deliversmaterial systematically and enhances students understanding of key concepts inthe subject.